Os impactos da abertura comercial sobre a remuneração relativa do trabalho no Brasil - Ana Flavia Machado; Mauricio Mesquita Moreira (Economia Aplicada, 2001)
The aim ofthis paper is to study the impacts oftrade liberalization on employment and workers' earnings in Brazil from 1985 to 1997. The main data source come from National Household Surveys (PNAD) accomplished by the Bureau of Statistics (IBGE). The theoretical referential is the Heckscher-Ohlin model and the StolperSamuelson theorem. The research shows that in Brazil there was not significant shift in the workers' relative employment or any relevant inequality of revenues deterioration, unlike observed in other Latin American countries.